Intracellular Infection by the Human Granulocytic Ehrlichiosis Agent Inhibits Human Neutrophil Apoptosis - Yoshiie, Kiyotaka (American Society for Microbiology, 2000)
In patients with human granulocytic ehrlichiosis (HGE), the HGE agent has been seen only in the peripheral blood granulocytes, which have a life span too short for ehrlichial proliferation. To determine if the HGE agent delays the apoptosis of human peripheral blood neutrophils for its advantage, peripheral blood granulocytes consisting mostly of neutrophils were incubated with freshly freed host cell-free HGE agent in vitro. The HGE agent induced a significant delay in morphological apoptosis and the cytoplasmic appearance of histone-associated DNA fragments in the granulocytes. This antiapoptotic effect was dose dependent. Although much weaker than the HGE agent freshly freed from the host cells, noninfectious purified HGE agent stored frozen and thawed also had antiapoptotic effect, which was lost with proteinase K treatment but not with periodate treatment. Treatment of neutrophils with a transglutaminase inhibitor, monodansylcadaverine, blocked the antiapoptotic effect of the HGE agent. Addition of oxytetracycline, however, did not prevent or reverse the antiapoptotic effect of the HGE agent. These results suggest that binding of a protein component(s) of the HGE agent to neutrophils and subsequent cross-linking and/or internalization of the receptor and ehrlichiae are required for antiapoptotic signaling, but ehrlichial protein synthesis and/or proliferation is not required. MG-132, a proteasome inhibitor, and cycloheximide accelerated the apoptosis of neutrophils and overrode the antiapoptotic effect of the HGE agent. Studies with specific inhibitors suggest that protein kinase A, NF-κB, and interleukin 1β are not involved in the antiapoptotic mechanism of the HGE agent.